Semirigid Ureteroscopy with Pneumatic Lithotripsy for Ureteral Stone - Dongol, UMS; Acharya, L; Subba, K; Khambu, B; Joshi, R; Shrestha, S K; Singh, DR (Journal of Nepal Health Research Council, 2011)
Background: Ureteral stones present with acute loin to groin pain. The objective of this study is to find out the outcome and safety of semi-rigid ureterscopy with pneumatic lithotripsy for treatment of ureteral stones of >30 mm2 and to assess the impact of size and location on stone free (SF) rate. Methods: Total 110 patients with isolated ureteral stone size>30 mm2 were included in this study and treated with pneumatic lithotripsy using 8/9.8 Fr. Semi-rigid ureteroscope (Stiema Germany). Stones were fragmented into 2-3mm particles and removed. Outcome parameters assessed at 3 months follow up were stone free rate(SF), Efficiency Quotient (EQ), and impact of stone size and site on SF/EQ was also analyzed. Similarly, patient demographics, procedures, patient related parameters and complications were also noted. Results: The overall SF rate at 3 months follow up was 69.33% and efficient Quotient (EQ) 52.52%. The SF/EQ for upper, middle and lower third of ureteral stone was 55/37.67,6/43.57, 92/84.40 respectively (P-value< 0.001). The SF for stone size 30-110 mm2 and >110mm2was 78% and 67% respectively. There were no major complications seen. Overall minor complication rate was 5.45 % (minor ureteral perforations-5, urinoma formation 1). Conclusions: Semi-rigid ureteroscopy with pneumatic lithotripsy is a safe, simple and effective procedure for ureteral stones with excellent success rate for distal ureteral stones. The stone free rate and EQ are statistically significant (P value<0.001) between upper, middle and lower ureteral stones. Stone size has a direct impact on the SF rate and EQ. Keywords: semirigid uerteroscopy, pneumatic lithotripsy.